Mathai-Haubold Interval Entropy and Related Inequalities (European Journal of Pure and Applied Mathematics, 2025)
The paper introduces a generalized interval entropy measure that provides a comprehensive framework for understanding and quantifying the uncertainty in systems with doubly truncated random variables. By characterizing well-known lifetime distributions (exponential, Pareto, and finite range distributions), deriving a lower bound for the entropy, and exploring stochastic comparisons, the paper demonstrates the usefulness of this measure in reliability modelling, survival analysis and information theory.
Keywords: Entropy, residual entropy, Interval entropy, Generalized failure rate, Characterization